2016
DOI: 10.1136/bmjopen-2016-012361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinicians' knowledge and practices regarding medical radiological exposure: findings from a mixed-methods investigation (survey and qualitative study)

Abstract: ObjectivesTo assess the impact of initiatives aiming to increase clinician awareness of radiation exposure; to explore the challenges they face when communicating with patients; to study what they think is the most appropriate way of communicating the long-term potential risks of medical radiological exposure to patients.DesignA quantitative and qualitative evaluation through a survey and focal groups.SettingSan Juan Hospital and Dr Peset Hospital (Southeast Spain) and clinicians from Spanish scientific societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Workers who specialize in radiology and cardiology may have more radiation safety education than in other specialties because they are more frequently involved in the performance of fluoroscopically-guided interventional procedures. Radiologists have received more training and more knowledge on radiation exposure compared with doctors of other medical specialties in Spain [ 18 ] and the US [ 19 ], and radiologists reported a higher accuracy of radiation doses associated with a standard chest x-ray exposure than non-radiologists in Hong Kong [ 20 ]. However, orthopedic surgeons less frequently wore a dosimeter (29.2%) compared with doctors with other specialties and did not apply the standard rules for radiation safety in South Korea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Workers who specialize in radiology and cardiology may have more radiation safety education than in other specialties because they are more frequently involved in the performance of fluoroscopically-guided interventional procedures. Radiologists have received more training and more knowledge on radiation exposure compared with doctors of other medical specialties in Spain [ 18 ] and the US [ 19 ], and radiologists reported a higher accuracy of radiation doses associated with a standard chest x-ray exposure than non-radiologists in Hong Kong [ 20 ]. However, orthopedic surgeons less frequently wore a dosimeter (29.2%) compared with doctors with other specialties and did not apply the standard rules for radiation safety in South Korea [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 Wider availability and local modification of the National Radiological Protection Board patient information leaflet may go some way in redressing this knowledge deficit. Innovative approaches such as incorporating the radiation dose of the scan that patient is about to undergo on the appointment letter and medical report 22 will allow patients to track their radiation exposure due to radiological investigations personally. Further, explanation of radiation doses in terms of background radiation may go some way to improving patients' understanding of their radiation exposure with each scan, where each standard CT scan of the abdomen and pelvis exposes patients to a radiation dose equivalent to three years of background radiation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Other than inadequate education of the patient, the current literature demonstrates that the patients' suboptimal knowledge could possibly be attributed to patients not being well informed. With only 50% of the patients inquiring about radiation exposure, 91% 19 and 68.3% 22 of patients were not informed about radiation exposure, demonstrating that there is a need to improve communication between patients and medical staff.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, communication with patients regarding associated risk is essential to get a rational use of diagnostic imaging test, but there is a lack of knowledge in the general population regarding radiation exposure and the associated risks related to these tests 29 30. In addition, recent studies showed that most clinicians were unaware of radiation exposure associated with imaging tests31–33 and that less than 50% of the imaging tests carried out in clinical practice were considered appropriate according to the available recommendations and 29.1% of the total collective effective dose was associated with inappropriate imaging tests 34…”
Section: Discussionmentioning
confidence: 99%